PATENT PROTECTION FOR AGRICULTURAL TECHNOLOGICAL PRODUCTS AS AN EFFORT FOR THE ADVANCEMENT OF INDONESIAN AGRICULTURE - Sharon Gracale (Awang Long Law Review, 2022)
Patents are an important instrument in protecting innovation activities in the modern economy, especially in agriculture. Its systems foster increased innovation indirectly, by increasing the profit that can potentially be obtained from commercializing new technology. Seeing the development of agricultural technology that is growing rapidly, patent protection for agricultural equipment is very crucial. Therefore, this paper will examine and explain the impact of applying Article 20 of the Indonesian Patent Law, especially regarding the implementation of Patents in agriculture. This research is a type of library research that is juridical normative using the statute approach method. It is expected that this research able to contribute to the field of law, especially those related to Property Rights, especially regarding the study of issues related to the issue of patent ownership in agriculture.